(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The recognized relevance of combating malignant neoplasms has necessitated the implementation of a unique nationwide program to combat oncological diseases in the Russian Federation and the construction of a modern integrated system, from screening and early diagnosis to timely effective treatment, which will protect a person.